Can material asset reorganizations affect acquirers' debt financing costs? Evidence from the Chinese merger and acquisition market - Qingquan Tang; Hongwen Han (China Journal of Accounting Research, 2018)
In this paper, we investigate whether material asset reorganizations (MARs), a special form of merger and acquisition (M&A) transactions, can affect the acquirers' cost of debt financing. Further, we examine the effect of acquiring firms' accounting information quality on the cost of debt and on the association between MARs and debt costs. We predict that compared to conventional M&As, large-scale acquisitions through MARs can generate a much greater influx of assets from target firms. This raises the acquirers' asset collateral and thus reduces the cost of debt. Because the quality of accounting information is a key factor affecting the cost of debt, we suggest that it has a spillover effect on the debt-cost effect of MARs. Using M&A transactions by listed companies in the Chinese A-share market from 2008 to 2014 as our sample, we find that MARs are associated with a higher asset collateral and lower ex post cost of debt than conventional M&As. Furthermore, we show that the acquiring firms' accounting information quality has a significant negative effect on debt costs, and the negative association between MARs and the cost of debt is more pronounced when accounting information quality is higher.
Keywords: 650; Material asset reorganizations; Merger and acquisition; Accounting information quality; Asset collateral; Cost of debt financing